2013
DOI: 10.5251/ajsir.2013.4.2.231.237
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of spring water quality in Ebonyi South Zone and its health impact

Abstract: Studies were carried out between June through December, 2007 to evaluate the quality of rural water supply for drinking in Ebonyi South Zone of Ebonyi State, Nigeria. The rural communities of Ekoli Edda and Ozizza in Afikpo South L.G.A and parts of Okposi in Ohaozara L.G.A depend solely on spring water for their domestic needs. Samples from seven spring water sources in these areas were analyzed for some physico-chemical and microbial parameters by standard methods. Concentrations of some heavy metals; Cr, Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Improving access to safe drinking water can result in tangible benefits to health. The quality of drinking water has a powerful impact on public health and therefore, the effective monitoring and comprehensive assessment of public or community drinking water systems are crucial to protect the wellbeing of the public [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Improving access to safe drinking water can result in tangible benefits to health. The quality of drinking water has a powerful impact on public health and therefore, the effective monitoring and comprehensive assessment of public or community drinking water systems are crucial to protect the wellbeing of the public [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Higher concentration of iron in water sample may be due to the nature of the metal that is strongly absorbed to soil and more easily dissolved in minutely negligible amounts [24]. Similarly, several authors also observed nearly same concentration of heavy metals in their studies [25,26]. The bacteriological analysis of water plays a vital role as it helps to determine potability of water for drinking and other domestic purposes.…”
Section: Resultsmentioning
confidence: 99%
“…Nickel (Ni) ranged from -0.032 to 0.011 mg/l with an average value of -0.019 mg/l in Abakaliki [160] . Like F, Ni was not widely reported.…”
Section: Mg 2h O Mg Oh Hmentioning
confidence: 99%
“…The threshold for the effects of Cu in drinking water on the gastrointestinal tract occurs, but then there is still some hesitation concerning the long-term effects of Cu on sensitive populations, such as carriers of the gene for Wilson Disease and other metabolic disorders of copper homeostasis [159] . Iron (Fe) ranged from 0-28 mg/l with an average value of 3.98 mg/l [147,157,158,160,161] . Iron is available in natural freshwaters at levels ranging from 0.5 to 50mg/ l [159] .…”
Section: Mg 2h O Mg Oh Hmentioning
confidence: 99%